THE EFFECT OF ADMINISTRATION OF AN EQUAL DOSE OF DIFFERENT CLASSES OF PHYTOCHEMICALS ON HEME OXYGENASE-1 GENE AND PROTEIN EXPRESSION IN MICE LIVER - ABDULLAH, AZMAN; ALRAWAIQ, NADIA SALEM; ATIA, AHMED (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Heme oxygenase-1 (HO-1) is enzyme that possesses antioxidant, anti-inflammatory, and cytoprotective functions. Induction of HO-1 occurs as an adaptive and beneficial response to various injurious stimuli such as oxidative stress. This study is aimed at monitoring the effects of administration of equal doses (50 mg/kg) of sulforaphane (SFN), curcumin, quercetin, indole-3-carbinol, and butylated hydroxyanisole (BHA) for 14 days on the levels of liver HO-1 gene and protein expression in mice. Method: A total of 48 adult male ICR white mice (25–30 g) were divided into eight groups: Normal control group (n=6), SFN-treated group (n=6), quercetin-treated group (n=6), curcumin-treated group (n=6), BHA-treated group (n=6), indole-3-carbinol treated group (n=6), vehicle 1 control group (n=6), and vehicle 2 control group (n=6). All chemicals were administered intraperitoneally at a dose of 50 mg/kg for 14 days. Vehicle 1 (dimethyl sulfoxide, TweenTM 20, and normal saline at a ratio of 0.05:0.1:0.85) was used to dissolve SFN, quercetin, and curcumin. Vehicle 2 (corn oil) was used to dissolve indole-3-carbinol and BHA. At day 15, the animals were sacrificed and their livers were isolated. From the liver, total RNA was extracted, reverse transcribed and subjected to quantitative real‐time polymerase chain reaction to detect HO-1 gene expression. Agarose gel electrophoresis was also performed to verify the specificity of the amplification. HO-1 protein expression was determined by Western blotting. Results: HO-1 gene expression showed significant increase of 4.6±0.3, 3.6±0.2, 3.6±0.4, 3.3±0.3, and 3.0±0.4-fold and HO-1 protein expression showed significant increase of 2.3±0.2, 2.2±0.2, 2.2±0.1, 1.8±0.1, and 1.7±0.2-fold following treatment with 50 mg/kg of SFN, indole-3-carbinol, BHA, curcumin, and quercetin, respectively, compared to controls (p<0.05). Conclusion: At a dose of 50 mg/kg, SFN administration for 14 days resulted in the highest induction of HO-1 gene and protein expression level in mice liver, and quercetin the lowest.